An Event-based Middleware for Syntactical Interoperability in Internet of Things - Eko Sakti Pramukantoro; Husnul Anwari (Institute of Advanced Engineering and Science, 2018)
Internet of Things (IoT) connecting sensors or devices that record physical observations of the environment and a variety of applications or other Internet services. Along with the increasing number and diversity of devices connected, there arises a problem called interoperability. One type of interoperability is syntactical interoperability, where the IoT should be able to connect all devices through various data protocols. Based on this problem, we proposed a middleware that capable of supporting interoperability by providing a multi-protocol gateway between COAP, MQTT, and WebSocket. This middleware is developed using event-based architecture by implementing publish-subscribe pattern. We also developed a system to test the performance of middleware in terms of success rate and delay delivery of data. The system consists of temperature and humidity sensors using COAP and MQTT as a publisher and web application using WebSocket as a subscriber. The results for data transmission, either from sensors or MQTT COAP has a success rate above 90%, the average delay delivery of data from sensors COAP and MQTT below 1 second, for packet loss rate varied between 0% - 25%. The interoperability testing has been done using Interoperability assessment methodology and found out that ours is qualified.